Rust Diseases of Willow and Poplar 2005
DOI: 10.1079/9780851999999.0243
|View full text |Cite
|
Sign up to set email alerts
|

Mycoparasite Sphaerellopsis filum and its potential for biological control of willow rust.

Abstract: This chapter provides information on S. filum, particularly on its taxonomy, nomenclature, morphology (anamorph and teleomorph), natural occurrence, life cycle in willow plantations, pathogenicity on rusts, mode of action, storage, growth and sporulation on media, incubation period, survival on plant surface, spread in plantations, and potential for the biological control of rust in willow coppice plantations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…It is not yet certain whether the substantial genotypic diversity in S. filum is caused exclusively by mutation. Morphological examination of field samples (Pei & Yuan, 2005) suggested that, if the sexual stage exists in S. filum on willow rust, it may be infrequent. In October 1999 and 2000, rusted leaves and stem cankers were collected, both carrying abundant S. filum pycnidia, from the short strip.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not yet certain whether the substantial genotypic diversity in S. filum is caused exclusively by mutation. Morphological examination of field samples (Pei & Yuan, 2005) suggested that, if the sexual stage exists in S. filum on willow rust, it may be infrequent. In October 1999 and 2000, rusted leaves and stem cankers were collected, both carrying abundant S. filum pycnidia, from the short strip.…”
Section: Discussionmentioning
confidence: 99%
“…In October 1999 and 2000, rusted leaves and stem cankers were collected, both carrying abundant S. filum pycnidia, from the short strip. They were placed in muslin bags and left in the open to allow them to overwinter (Pei & Yuan, 2005). The S. filum fruiting bodies were examined at 1-2 months intervals until July.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conidia were stored at -60°C in a 15% glycerol solution. Conidial suspensions were transferred to PDA amended with 300 mg of Bacto Tryptone and 150 mg of Bacto Yeast Extract, and incubated for 2 days under UV light (40-W blacklight; GE, Fairfield, CT) at 23°C and then under gro-lights (40-W, Gro-Lux; Sylvania, Danvers, MA) at 23°C for 2 to 3 weeks (20). Mucilaginous cirrhi of conidia were harvested from pycnidia by means of a sterile blade and placed into centrifuge tubes with 1 ml of sterilized water containing 0.05 M MgS04 to help prolong viability of the conidia (unpublished data).…”
Section: Iviateriais and Iviethodsmentioning
confidence: 99%
“…Late-autumn plantings of perennial ryegrass have significantly less stem rust severity during the epidemic than those planted earlier in the fall, probably due to lower overwintering population of the pathogen (27). However, late planting results in a yield reduction, as demonstrated by a 23% lower seed yield compared with earlier planted stands when stem rust is kept equally low in both stand types through the use of fungicides (20). Reducing the overwintering P. graminis subsp.…”
mentioning
confidence: 98%